2015
DOI: 10.1039/c4cc08946d
|View full text |Cite
|
Sign up to set email alerts
|

Transfer hydrogenation of unsaturated bonds in the absence of base additives catalyzed by a cobalt-based heterogeneous catalyst

Abstract: A novel non-noble Co@C-N catalytic system has been developed for catalytic transfer hydrogenation reactions. Co@C-N was found to be highly active and selective in the hydrogenation of a variety of unsaturated bonds with isopropanol in the absence of base additives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(44 citation statements)
references
References 59 publications
0
43
0
1
Order By: Relevance
“…MOF‐derived materials also have been employed as heterogeneous catalysts for reduction reactions, such as unsaturated bonds hydrogenation, hydrogenation of diverse nitro compounds and so on. Li and co‐workers found that Co@C‐N materials derived from a Co‐containing MOF presented high activity and selectivity in the hydrogenation of a variety of unsaturated bonds, including CC, CC, NO, and CO bonds, with isopropyl alcohol in the absence of any base additives . The Cu 3 (BTC) 2 was used as both sacrificial template and copper precursor to give Cu/Cu 2 O composite for catalytic reduction of 4‐nitrophenol (4‐NP) to 4‐aminophenol (4‐AP) by NaBH 4 .…”
Section: Mofs For Heterogeneous Catalysismentioning
confidence: 99%
“…MOF‐derived materials also have been employed as heterogeneous catalysts for reduction reactions, such as unsaturated bonds hydrogenation, hydrogenation of diverse nitro compounds and so on. Li and co‐workers found that Co@C‐N materials derived from a Co‐containing MOF presented high activity and selectivity in the hydrogenation of a variety of unsaturated bonds, including CC, CC, NO, and CO bonds, with isopropyl alcohol in the absence of any base additives . The Cu 3 (BTC) 2 was used as both sacrificial template and copper precursor to give Cu/Cu 2 O composite for catalytic reduction of 4‐nitrophenol (4‐NP) to 4‐aminophenol (4‐AP) by NaBH 4 .…”
Section: Mofs For Heterogeneous Catalysismentioning
confidence: 99%
“…[184] Similar complexes with hemilabile OMe or pyridine ligands [185] [191] Some cobalt examples have recently been published; cobalt on a heterogeneous support was used in TH of C=O, C=N and C=C bonds using IPA as the reducing agent. [192] A cobalt catalyst containing a 'PNP' donor structure was used in ATH of a number of imines although the focus was on ketones and aldehydes. [193] Nickel nanoparticles have also been used in imino TH.…”
Section: Diastereoselective Asymmetric Reductionsmentioning
confidence: 99%
“…Among the various dopants, nitrogen attracted most interest [15,[20][21][22]. and applications of transition metal/N-doped graphene (NGr) based catalytic systems ranges from oxygen reduction reactions (ORR) [23][24][25][26], hydrogen evolving reactions (HER) [27,28], photocatalysis [29,30], oxidation [31][32][33][34][35][36][37][38], and reduction [39][40][41][42][43][44] reactions of organic …”
mentioning
confidence: 99%